Effect of phospholipids and their molecular species on cholesterol solubility and nucleation in human and model biles. Issue 1 (January 1993) - Halpern, Z; Moshkowitz, M; Laufer, H; Peled, Y; Gilat, T
Abstract : Much research in the pathophysiology of gall stones has been devoted to various molecular species of bile salts. Recent findings have shown the importance of phospholipids in biliary pathophysiology. In the present study the addition of increasing doses of egg lecithin to human and model biles progressively prolonged the nucleation time. Concurrently biliary cholesterol was shifted from the vesicular to the non-vesicular carrier(s) while the cholesterol/phospholipid ratio of the remaining vesicles was progressively lowered. Model bile solutions of identical lipid concentration were prepared using phosphatidylcholine, phosphatidylserine, and phosphatidylethanolamine as the only phospholipid. With phosphatidylethanolamine most of the cholesterol was shifted to the vesicular carrier while phosphatidylserine shifted most of the cholesterol to the non-vesicular carrier(s). With phosphatidylcholine the cholesterol was distributed in both carriers. Phosphatidyl choline species composed of various acyl fatty acids in the sn-1 and sn-2 positions were used as the sole phospholipid in otherwise identical model bile solutions. With palmitic acid in the sn-1 position and arachidonic acid in the sn-2 position most of the cholesterol was found in the non-vesicular carrier. When stearic acid was used in sn-2 position instead of arachidonic acid most of the cholesterol was found in the vesicular carrier. These and other variations in phospholipid molecular species shifted cholesterol among its carriers and also modified the nucleation time of model biles. Most of these effects were also found upon addition of the various phospholipid species to human biles. These findings show the importance of phospholipid species in biliary pathophysiology and may be useful when trying to manipulate cholesterol carriers and solubility in bile.